Analisis pendapatan dan pola konsumsi nelayan pancing ulur di Desa Waturambaha Kecamatan Lasolo Kepulauan Kabupaten Konawe Utara - Hardianti, Wa Ode; Yusuf, Sarini; Rosmawati (Universitas Halu Oleo, 2021)
The study was conducted in Waturambaha Village, District of Lasolo Islands, North Konawe from June to July 2019. The aim of study was to know fishing rod fishermen income on consumption expenditure allocation and consumption pattern of household consumption pattern. The respondents of the study were 17 fishing rod fishermen. Sampling was taken using simple random sampling technique. Data was obtained through interview according to questionnaire provided. The variables measured and observed were fix cost and variable cost used for fish capture activity, income and other expenditures of food and non-food of fishermen.The results of study showed the highest income of fisherman was Rp 6,052,750/month and the lowest was Rp 2,980,250. The consumption expenditure pattern showed the average for household food and non-food was Rp 1,127,529/month and Rp 1,442,647/month, respectively.Net income of the fishing rod fishermen gained was average Rp 4,351,060/month, while consumption expenditure was average Rp 2,570,170/month. Consumption expenditure consisted of expenditure for food and non-food. Expenditure for non-food was higher 71% than for food. Those fishermen household is categorized as prosterous fishermen household.